2005
DOI: 10.1007/s11065-005-3585-5
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Perspective Perceptual Disorder of the Right Hemisphere

Abstract: Traditional accounts of right-posterior brain injury describe a syndrome of low-level perceptual sequelae producing marked acute dependency and transient safety concerns. The syndrome is also held to spare cognition and to carry a generally favorable long-term prognosis. The present paper reviews publications and anecdotal data that challenge this picture. Recent theoretical expositions and empirical studies stipulate three major cognitive functions of the right posterior association cortex: processing novel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 188 publications
0
7
0
Order By: Relevance
“…Increased right hemisphere activation has several important consequences: it promotes social-emotional information processing (Tranel et al 2002); it forefronts negative appraisal systems (Cacioppo et al 2002); and, it elicits holistic, gestalt thinking. Recent research has also shown that the right posterior association cortex is particularly important in the processing of new information, as well as in anticipating consequences and determining emergency reactions (Schutz 2005). Ritual's ability to engage these various right hemispheric functions, and its promotion of associational learning and strengthening of long-term memory would be particularly important in relation to complex social decisions involving unrelated and potentially dangerous conspecifics.…”
Section: Open Peer Commentarymentioning
confidence: 99%
“…Increased right hemisphere activation has several important consequences: it promotes social-emotional information processing (Tranel et al 2002); it forefronts negative appraisal systems (Cacioppo et al 2002); and, it elicits holistic, gestalt thinking. Recent research has also shown that the right posterior association cortex is particularly important in the processing of new information, as well as in anticipating consequences and determining emergency reactions (Schutz 2005). Ritual's ability to engage these various right hemispheric functions, and its promotion of associational learning and strengthening of long-term memory would be particularly important in relation to complex social decisions involving unrelated and potentially dangerous conspecifics.…”
Section: Open Peer Commentarymentioning
confidence: 99%
“…This synchronization is registered in the firing patterns of the stress‐sensitive corticolimbic regions of the right brain, dominant for coping with negative affects (Davidson et al ., 1990). Describing the essential survival functions of this lateralized system, Schutz (2005) notes “The right hemisphere operates a distributed network for rapid responding to danger and other urgent problems. It preferentially processes environmental challenge, stress and pain and manages self‐protective responses such as avoidance and escape.” The right brain is fundamentally involved in an avoidant‐defensive mechanism for coping with emotional stress, including the passive survival strategy of dissociation.…”
Section: Self‐psychological Models Of Psychopathogenesis: Negative Immentioning
confidence: 99%
“…The left hemisphere is less concerned about others and their feelings. Neuropsychologist Larry Schutz comments that, absent the right hemisphere, social intercourse is conducted with a total disregard for the feelings, needs, and expectations of others (2005). These discoveries about the way the parts of the brain function is important information for theological ethicists to consider in light of the fact that concern for others is the very bedrock of the activity of theological ethics.…”
Section: The Bicameral Brainmentioning
confidence: 99%